HUBUNGAN EMOSI DENGAN MOTIVASI BELAJAR PESERTA DIDIK KELAS XI DI SMA N 13 PADANG - Dariani, Fera - (Bimbingan dan Konseling, 2014)
This research describe about student emotion, studying motivation of student and therelationship between emotion and studying of student in SMAN 13 Padang. The type of thisresearch is descriptive and quantitative research with statistic analysis co relational with studentpopulation in class XI SMAN 13 Padang is 284 student and 65 sample. The sample taking useproporsional random sampling technique. The tool which is used to collect data is likequestionnaire. To analyze the data of emotion and studying motivation of student by usingpercentage analysis technique, meanwhile in testing hypothesis to see the relationship betweenmotivation and emotion of student by using formula Pearson Product Moment Correlation, thecalculation using SPSS version 16.0. The data analysis result are : (1) the emotion of student is inwell category, (2) student motivation is in enough category. (3) the relationship of emotion andstudying motivation is gotten r count 0,402> r table 0,234 with significant level 0,01 (sig<0,05).So based on the result of the research is gotten that there is relationship between emotion andstudying motivation in class XI SMAN 13 Padang.